Experimental analysis of a flat plate solar collector with integrated latent heat thermal storage - Mauricio Carmona; Mario Palacio; Arnold Martínez (Journal of Contemporary Urban Affairs, 2017)
In the present paper, an experimental analysis of a solar water heating collector with an integrated latent heat storage unit is presented. With the purpose to determine the performance of a device on a lab scale, but with commercial features, a flat plate solar collector with phase change material (PCM) containers under the absorber plate was constructed and tested. PCM used was a commercial semi-refined light paraffin with a melting point of 60°C. Tests were carried out in outdoor conditions from October 2016 to March 2017 starting at 7:00 AM until the collector does not transfer heat to the water after sunset. Performance variables as water inlet temperature, outlet temperature, mass flow and solar radiation were measured in order to determine a useful heat and collector efficiency. Furthermore, the operating temperatures of the glass cover, air gap, absorber plate, and PCM containers are presented. Other external variables as ambient temperature, humidity and wind speed were measured with a weather station located next to the collector. The developed prototype reached an average thermal efficiency of 24.11% and a maximum outlet temperature of 50°C. Results indicate that the absorber plate reached the PCM melting point in a few cases, this suggests that the use of a PCM with a lower melting point could be a potential strategy to increase thermal storage. Thermal analysis and conclusions of the device performance are discussed.